(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to determine C-reactive protein (CRP) levels in patients with intervertebral disc disease (IDD) and to evaluate these patients’ radiological and clinical characteristics. Material and Methods: A total of 102 patients were divided into four groups according to lumbar MRI results using the Macnab classification: bulging, protrusion, extrusion-sequestration, and normal. Straight leg raising test (SLR) and visual analogue scale (VAS) were used for clinical evaluation. Patients with bulging and protrusion were treated with conservative therapy within 5-10 days and bed-rest. Blood samples, SLR values and VAS scores were obtained from these patients before and after conservative therapy. The extrusion-sequestration group underwent lumbar spinal surgery. Medical treatment was not applied to this group and blood samples were collected only preoperatively. Individuals with normal MRI findings and no spinal complaints were evaluated as controls. Results: CRP levels were found to be 6.61 ± 7.78 in controls, 6.62 ± 5.28 in the bulging group, 11.50 ± 21.71 in the protrusion group and 17.18 ± 48.22 in the extruded-sequestration group (p=0.321). CRP levels were significantly decreased after treatment in the bulging group (p=0.001). Positive correlations were found between post-treatment VAS scores and pre-treatment WBC in the protrusion group, and with CRP levels in the bulging group. Conclusion: Although no statistically significant difference was determined, we observed higher mean serum CRP levels in the surgical group (extrusion-sequestration). We believe that further studies must be performed to determine whether serum CRP levels can be used as a prognostic marker in surgical decision making.